Efektivitas Makanan Berbasis Lokal Tawas Ut (Ampelocissus Rubuginosa L) Terhadap Status Kesehatan Ibu Post-Partum Di Kota Palangka Raya: The Effectiveness of Local-Based Foods of Tawas Ut (Ampelocissus Rubuginosa L) on the Health Status of Post Partum Mothers in Palangka Raya - Aden, Christine; Heriteluna, Marselinus (Jurnal Surya Medika (JSM), 2020)
Postpartum recovery of the reproductive organs, especially the uterus, should occur immediately. The uterus should return to its pre-pregnancy size. Treatment to restore maternal health during the postpartum period was carried out by the Dayak community by using the herbal concoction of Tawas Ut (Ampelocissus Rubuginosa L). This study aims to determine the health status of post-partum mothers by administering the Tawas Ut herb as a food product. paired t-test). It was found that there was a significant difference in the mean fundal height between the intervention and control groups (p-value 0.012) with a difference of 2.91, or there was a difference of 61.1%. The results of the Paired t-test showed that there was a significant difference in the mean uterine fundal height between before and after the intervention period (p-value 0.0005) with a difference in uterine fundal height of 10.45 cm or a change of 84%. This shows that the local-based food of Tawas Ut has effects on the health status of postpartum mothers, which can reduce leukocytes by 32% and reduce uterine fundal height by 84% to normal sizes as before pregnancy. The use of this product is recommended to be used as a companion to standard service programs for postpartum mothers to support government programs to reduce maternal morbidity and mortality due to postpartum problems.